Government regulation of private health insurance - Motaze, Nkengafac Villyen (Cochrane Database Syst Rev, 2021)
BACKGROUND: The strain on public resources to meet the healthcare needs of populations through publicly‐provided health insurance programmes is increasing and many governments turn to private health insurance (PHI) to ease the pressure on government budgets. With the goal of improving access to basic health care for citizens through PHI programmes, several high‐income countries have developed strong regulations for PHI schemes. Low‐ and middle‐income countries have the opportunity to learn from this experience to optimise PHI. If poorly regulated, PHI can hardly achieve an adequate quantity or quality of population coverage, as can be seen in the USA where a third of adults younger than 65 years of age have no insurance, sporadic coverage or coverage that exposes them to high out‐of‐pocket healthcare costs. OBJECTIVES: To assess the effects of policies that regulate private health insurance on utilisation, quality, and cost of health care provided. SEARCH METHODS: In November 2019 we searched CENTRAL; MEDLINE; Embase; Sociological Abstracts and Social Services Abstracts; ICTRP; ClinicalTrials.gov; and Web of Science Core Collection for papers that have cited the included studies. This complemented the search conducted in February 2017 in IBSS; EconLit; and Global Health. We also searched selected grey literature databases and web‐sites.  SELECTION CRITERIA: Randomised trials, non‐randomised trials, interrupted time series (ITS) studies, and controlled before‐after (CBA) studies conducted in any population or setting that assessed one or more of the following interventions that governments use to regulate private health insurance: legislation and licensing, monitoring, auditing, and intelligence. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed study eligibility, extracted data, and assessed risk of bias and certainty of the evidence resolving discrepancies by consensus. We planned to summarise the results (using random‐effects or fixed‐effect meta‐analysis) to produce an overall summary if an average intervention effect across studies was considered meaningful, and we would have discussed the implications of any differences in intervention effects across studies. However, due to the nature of the data obtained, we have provided a narrative synthesis of the findings. MAIN RESULTS: We included seven CBA studies, conducted in the USA, and that directly assessed state laws on cancer screening. Only for‐profit PHI schemes were addressed in the included studies and no study addressed other types of PHI (community and not for‐profit). The seven studies were assessed as having 'unclear risk' of bias. All seven studies reported on utilisation of healthcare services, and one study reported on costs. None of the included studies reported on quality of health care and patient health outcomes. We assessed the certainty of evidence for patient health outcomes, and utilisation and costs of healthcare services as very low. Therefore, we are uncertain of the effects of government mandates on for‐profit PHI schemes. AUTHORS' CONCLUSIONS: Our review suggests that, from currently available evidence, it is uncertain whether policies that regulate private health insurance have an effect on utilisation of healthcare services, costs, quality of care, or patient health outcomes. The findings come from studies conducted in the USA and might therefore not be applicable to other countries; since the regulatory environment could be different. Studies are required in countries at different income levels because the effects of government regulation of PHI are likely to differ across these income and health system settings. Further studies should assess the different types of regulation (including regulation and licensing, monitoring, auditing, and intelligence). While regulatory research on PHI remains relatively scanty, future research can draw on the rich body of research on the regulation of other health financing interventions such as user fees and results‐based provider payments.